Design and Investigate of Flushing System for Electrical Discharge Machining (EDM) Application - Rachmat, Haris; Ibrahim, Mohd. Rasidi (International Journal of Integrated Engineering, 2020)
Electrical Discharge Machining (EDM) is high precision machining process in which no actual contact between the workpiece and electrode during sparking. Dielectric fluid play a role as flushing medium and semiconductor between workpiece and electrode to stabilization and controlled spark gap ionization condition. In real condition, nozzle flushing system in EDM machine not able to complete remove debris formed during machining and affect the machining performance. Improper flushing due to lack of guideline at setup position of nozzle and inlet pressure caused low material removal rate, irregular tool and higher cost on raw material. To overcome this problem, the design and investigate of flushing system in EDM application is required. The design and investigation undergo by simulation of ANSYS Computational Fluid Dynamics (CFD) with a virtual experiment to accurate prediction of flushing performance. The influence of nozzle size and inlet pressure supplied on flushing efficiency were analyzed to avoid improper flushing on die-sinking EDM process. The simulation and experiments clarified that the higher inlet pressure, P=0.20 bar and larger nozzle diameter, D=6mm resulting in higher total pressure which is 2647.16 Pa. Furthermore, the streamline of velocity and eddy viscosity contour in the work tank using to analyze the turbulence zone by nozzle flushing obtained by the CFD analysis. The condition in case 5 (D=5mm, P=0.15 bar) is more efficiency on debris removal rate based on the result of high total pressure on machining zone and eddy viscosity contour showed the turbulence zone only formed area near to outlet of system. The model results have been shown good agreement with experiment and co-relation data.